Initial evaluation of Cu-64 labeled PARPi-DOTA PET imaging in mice with mesothelioma - Huang, Tao (Bioorg Med Chem Lett, 2017)
Poly(ADP-ribose) polymerase (PARP) has emerged as an important molecular target for the treatment of several oncological diseases. A couple of molecular probes based on Olaparib scaffold have been developed by incorporation of F-18 or fluorophore for positron emission tomography (PET) or optical imaging in several types of tumor. PARP has been reported overexpressed in mesothelioma. We hereby synthesized an analogue of Olaparib containing DOTA moiety and radiolabeled it with Cu-64 to evaluate its utility of PET tracer for mesothelioma. The Cu-64 labeling was conveniently achieved at 90% yield with final compound at >99% radiochemistry purity. The biodistribution and PET imaging were performed at 0.5, 1, 2 and 18 h to confirm the in vivo tumor targeting. The tumor uptake in study group was significant higher than that in control group (3.45 ± 0.47% ID/g vs 2.26 ± 0.30% ID/g) and tumor were clearly detected by PET imaging. These results suggest the feasibility to develop an Olaparib-based theranostic agent for mesothelioma.